On Blinking - Fernando, Jeremy; Hannis, Sarah Brigid (punctum books, 2012)
On Blinking opens a dossier on seeing. It looks not only to the epistemological sense of what it means to see or the hermeneutical sense of what is the meaning of that which is seen but attends to various sites of knowledge - photography, literature, and philosophy. And in doing so, it questions the privileging of presence and sight in Western thought. Thus, this book, through the essays - "Emerging Sight, Emerging Blindness" (Brian Willems); "Augen, Blicke, Stätten" (Julia Hölzl); "At the Risk of Love" (Jeremy Fernando); and "Suspended in a Moving Night: Photography, or the Shiny Relation Self-World" (Jessica Aliaga Lavrijsen) - attempts to address the question what is seeing.